HLA-B*1502 Increases the Risk of Phenytoin or Lamotrigine Induced Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis: Evidence from a Meta-analysis of Nine Case-control Studies - Li, X.; Yu, K.; Mei, S.; Huo, J.; Wang, J.; Zhu, Y.; Zhao, Z. (Drug Research, 2015)
Background and Study aims: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are fatal adverse cutaneous drug reactions which may be induced by phenytoin (PHT) or lamotrigine (LTG). The objective of this study was to analyze the association of human leukocyte antigen (HLA)-B*1502 and PHT or LTG induced SJS/TEN.Patients and Methods: All the participants were epileptic patients and the SJS/TEN were induced by PHT or LTG. The presence or absence of the HLA-B*1502 allele of all the patients was determined. ISI Web of Knowledge, PubMed, ScienceDirect, EMBASE, and Cochrane Register of Controlled Trials (CENTRAL) data were searched for the literature published before April 2014. Meta-analysis was performed using Review Manager 5.2 software.Results: From 256 citations, 6 English studies were included that involved 480 epilepsy patients. Meta-analysis showed that odd ratio (OR) of PHT and LTG were 5.65 [95% CI: 2.76–11.57] and 4.51 [95% CI: 1.57–12.98], respectively. Funnel plot analysis showed symmetry, indicting less possible publication bias and the results were partly reliable.Conclusion: There is a significant association between HLA-B*1502 and PHT or LTG-induced SJS/TEN.
Keywords: phenytoin; lamotrigine; HLA-B*1502; meta-analysis; Stevens-Johnson syndrome; toxic epidermal necrolysis